2005
DOI: 10.1192/apt.11.5.362
|View full text |Cite
|
Sign up to set email alerts
|

The management of violence in general psychiatry

Abstract: This is the first of two complementary articles in APT that (Macpherson et al, 2005). There is deliberate overlap between the two articles, which will allow each to be read independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 14 publications
2
48
1
1
Order By: Relevance
“…The largest British study 4 pertinent to this question to date was conducted in 2007 -a year after the NICE guidelines were released. This study assessed the prevalence of untreated cardiovascular risk factors out of a cohort of 1966 patients in assertive outreach teams.…”
Section: About the Authorsmentioning
confidence: 99%
“…The largest British study 4 pertinent to this question to date was conducted in 2007 -a year after the NICE guidelines were released. This study assessed the prevalence of untreated cardiovascular risk factors out of a cohort of 1966 patients in assertive outreach teams.…”
Section: About the Authorsmentioning
confidence: 99%
“…16 Previous studies have found women in hospital settings to be more frequently involved in violent incidents than their male counterparts, but that men are more likely to cause injury. 17 As evident from earlier studies, staff members were more likely than patients to be victims of assault, with doctors being assaulted least frequently. This could be a reflection of the perceived status of the doctor.…”
Section: Discussionmentioning
confidence: 67%
“…La formation du personnel soignant dans les techniques de désescalade ainsi que l'expérience clinique dans l'évaluation des risques sont des éléments essentiels de prévention de la violence dans les unités de soins [19]. Elles constituent dès lors des pistes pour diminuer le recours à l'isolement.…”
Section: Les Mesures Alternativesunclassified